SKIN CANCER - Made Putri Hendaria; AAGN Asmarajaya; Sri Maliawan (Universitas Udayana, 2013)
Skin is an organ which protect the human body from the environment. It was build by milion cells. According to the changes in human lifestyle which tends to unhealthy life, increasing ultraviolet radiation, toxins, and genetics makes the cells who build the skin do the abnormal growth being cancer cells. Classification of skin cancer is according the most common three types, they are Basal Cell Carcinoma, Squamous Cell Carcinoma, and Malignant Melanoma. More than 3,5 milion skin cancer cases was happened in United States, which makes it become the most common cancer type in that country. Skin cancer diagnosis is build from anamnesis, physic examination about skin eufloressence, using dermoscopy, and histopatologic examination as the gold standar. Therapy for skin cancer is classified to surgery and non surgery therapy and its prognostic is depend to the types of the skin cancer itself.